Quaternized Poly(4-vinylpyridine-co-N-2-hydroxypropylmethacrylamide) and antibacterial peptide linear conjugates: Synthesis, characterization, and bioactivity - Ozburun, Damla Gokkaya; Hancer, Hande; Findikli, Buse; Ozbek, Tulin; Ozmen, Mehmet Murat; Topuzogullari, Murat (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Cationic polymers and antibacterial peptides are effective in combating infections caused by bacteria. Although both materials can naturally exhibit antibacterial effects due to the disruption of the bacterial membrane, their combination can further enhance their properties. For instance, polymer-peptide conjugates can reduce the toxicity that cationic polymers exhibit against mammalian cells. In this study, poly(4-vinylpyridine-co-N-2hydroxypropylmethacrylamide) copolymer was RAFT-synthesized and conjugated to the antibacterial peptide of RWWRWWR through their chain ends via maleimide-thiol reaction. Subsequently, the pyridine groups of the produced linear conjugates were quaternized to obtain a novel conjugate of the antibacterial polycation and the antibacterial peptide. The structural characterization results acquired from FTIR, NMR, fluorescence spectroscopy and GPC revealed the successful synthesis of both the copolymer and the conjugate. The biological activity of the conjugate was evaluated on both bacteria and mammalian cells. The results indicated that reduced toxicity was achieved in the case of the conjugate compared to the copolymer, while the antibacterial activity of the conjugate against both E. coli and S. aureus was still maintained.
Keywords: Antibacterial; Conjugate; Peptide; Polycation; Quaternization; RAFT polymerization; ANTIMICROBIAL PEPTIDES; PROTEINS; DESIGN; Polymer Science